Sustainable Shopping : Kain Perca sebagai Tote Bag untuk Mendukung UMKM Olahan Ikan di Kampung Nelayan Desa Salira - Aryati Aryati; Munawaroh Munawaroh (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This community service activity aims to provide education about the use of shopping bags (totebags) from patchwork waste as an alternative to plastic bags to MSME business actors processed fish in Kampung Nelayan Desa Salira. The method used by the author in this activity begins with providing training on plastic bag waste, then also an introduction to the utilization of fabric waste that can be reused to make new products that are useful and ends with the handover of helanja bags to the business actors of processed fish MSMEs in Kampung Nelayan Desa Salira. The processed fish MSME products are in the form of payus fish amplang crackers, fish rolade, fish nuggets, fish meatballs made from fish, and in their sales require reusable shopping bags and have product selling value.